A systematic review and meta-analysis of drug-coated balloons versus drug-eluting stents in de novo and in-stent restenosis coronary bifurcation lesions - Dzikrul Haq Karimullah, Muchammad; Saputra, Pandit Bagus Tri; Alkaff, Firas Farisi; Oktaviono, Yudi Her; Nugraha, Ricardo Adrian; Faizah, Novia Nurul; Widiarti, Wynne; Aufazhafarin, Nadhifa Tanesha; Doman, Zahras Azimuth; Sahara, Rendy Asmaradhana; Niazta, Nisa Amnifolia (Heart Science Journal, 2026)
Background: Coronary bifurcation lesions are notoriously difficult to treat percutaneously and may require advanced techniques. Drug-eluting balloons (DCBs) have several advantages over drug-eluting stents (DESs), including the ability to maintain arterial physiology, reduce the risk of stent thrombosis, and eliminate the need for permanent metal implants. However, it remains uncertain which treatment will work best. Objective: This study evaluated DCBs and DESs in coronary bifurcation lesions using subgroup analyses based on lesion type and location. Methods: We searched scientific databases for relevant publications up until May 31, 2025. In order to synthesise the results, a random-effects model was employed. To determine the possibility of bias, the ROBINS-I was utilized, and to measure the level of heterogeneity across the studies, the I³ statistic was used. Results were analyzed clinically and angiographically. This subgroup analysis focused on the position of the bifurcation and the kind of lesion (new, internal, or all sites). Result: Eleven research were deemed eligible for inclusion. There was a trend toward fewer major adverse cardiac events (MACE) with DCB compared to DES in the whole cohort, however the trend was not statistically significant (OR0.77, 95% CI0.58-1.02; p=0.07; I²=0%). Both major adverse cardiac events (MACE) and target lesion revascularization (TLR) were significantly reduced in de novo bifurcations when DCB was used (OR0.61, 95% CI 0.41-0.89; p=0.01). Myocardial infarction, target vessel revascularization, in-stent thrombosis, and cardiac mortality were not significantly different among groups. Both the early and late lumen loss and gain seen on angiograms were within the normal range. Conclusion: In de novo bifurcation lesions, DCB demonstrates reduced MACE and TLR versus DES, supporting its role as a stent-free alternative. Randomized controlled trials with greater sample sizes and prolonged follow-up are warranted.